Deploying triple artemisinin-based combination therapy (TACT) for malaria treatment in Africa: ethical and practical considerations - Tindana, P; de Haan, F; Amaratunga, C; Dhorda, M; van der Pluijm, RW; Dondorp, AM; Cheah, PY (BioMed Central, 2021)
Malaria remains a major cause of morbidity and mortality in Africa, particularly in children under five years of age. Availability of effective anti-malarial drug treatment is a cornerstone for malaria control and eventual malaria elimination. Artemisinin-based combination therapy (ACT) is worldwide the first-line treatment for uncomplicated falciparum malaria, but the ACT drugs are starting to fail in Southeast Asia because of drug resistance. Resistance to artemisinins and their partner drugs could spread from Southeast Asia to Africa or emerge locally, jeopardizing the progress made in malaria control with the increasing deployment of ACT in Africa. The development of triple artemisinin-based combination therapy (TACT) could contribute to mitigating the risks of artemisinin and partner drug resistance on the African continent. However, there are pertinent ethical and practical issues that ought to be taken into consideration. In this paper, the most important ethical tensions, some implementation practicalities and preliminary thoughts on addressing them are discussed. The discussion draws upon data from randomized clinical studies using TACT combined with ethical principles, published literature and lessons learned from the introduction of artemisinin-based combinations in African markets.